2016
DOI: 10.1016/j.jaut.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Human effector B lymphocytes express ARID3a and secrete interferon alpha

Abstract: Previously, we determined that enhanced disease activity in patients with systemic lupus erythematosus (SLE) was associated with dramatic increases in numbers of B lymphocytes expressing the transcription factor ARID3a. Our data now indicate ARID3a is important for interferon alpha (IFNa) expression and show a strong association between ARID3a expression and transcription of genes associated with lupus IFN signatures. Furthermore, both ARID3a and IFNa production were elicited in healthy control B cells upon st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 49 publications
3
47
1
1
Order By: Relevance
“…Circulating ARID3a + transitional and naïve B cells from SLE patients have been shown to express high levels of IFNα (19). Comparison of type I IFN expression in freshly isolated, FACS-sorted cells from BXD2 and age-matched B6 mice revealed significantly elevated levels of endogenous type I IFN genes in T1 but not in other subsets of B cells from BXD2 mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Circulating ARID3a + transitional and naïve B cells from SLE patients have been shown to express high levels of IFNα (19). Comparison of type I IFN expression in freshly isolated, FACS-sorted cells from BXD2 and age-matched B6 mice revealed significantly elevated levels of endogenous type I IFN genes in T1 but not in other subsets of B cells from BXD2 mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ARID3a has been linked to development of B-1 cells in mice, and hematopoietic stem cells from SLE patients with high levels of ARID3a in B cells when transferred to mice produced increased levels of autoantibodies (48). Moreover, innate and type I IFN pathways are markedly up-regulated in B cells with high levels of ARID3a (49). We found that ARID3a was up-regulated in BM-MSCs, and ARID3a mRNA was down-regulated in addition to IFNb mRNA when MAVS was silenced.…”
Section: Discussionmentioning
confidence: 99%
“…To unravel the mechanism behind the stimulatory effect of IFN-γ on CpG-induced IL-10, we studied the potential involvement of the type 1 IFNs IFN-α and IFN-β, since these have been described to increase TLR-induced IL-10 production in murine macrophages [64]. Interestingly, it has been reported that human B cells can produce IFN-α after stimulation with CpG class C [65]. However, while class A and class C CpG oligonucleotides are indeed potent inducers of type 1 IFNs, class B CpG (the one we used in our assays) is a weak inducer [66].…”
Section: Discussionmentioning
confidence: 99%